International exhibition of peace posters (Co-operative Retail Services Ltd.)
Reproduction of poster 'Youth demands peace', by artist Debby Lonnon Poster advertising exhibition held in London by the Co-operative Retail Services Ltd., London Region Political Committee PO-0382